PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR THE FAMILY WITH YOUNGER SCHOOLBOY WITH MENTAL RETARDATION - G. Yu. Taskina; I. A. Taskina (Вестник университета)
An urgent issue of modern education – the issue of psychological and pedagogical support for the family with a child with health disabilities has been considered. It has been specified, that particularly specially organized work can help parents and members of family with a child with health disabilities to cope with the difficulties of raising child and carry out his socialization. In particular, the results of a study of the personality of the parents of a child of primary school age with a mental retardation, their chosen style of child upbringing, the nature of interaction with the child have been presented. In addition, the effectiveness of the compiled and tested program of psychological and pedagogical support for the family with a child with a mental retardation, changes in the behavior of parents and children before and after testing the program have been analysed.